KESANTUNAN BERBAHASA DAN PELANGGARANNYA DALAM CHANNEL YOUTUBE DEDDY CORBUZIER EDISI SITI FADILAH : SEBUAH KONSPIRASI - Itznaniyah Umie Murniatie (Universitas Islam Malang, 2021)
One of the goals of communicating is to be able to establish social relations with the community, so as to create success in the communication process. The expression of politeness in a communication process, can be a determinant of the quality of a person's attitude, mainly, the speaker. Or in other words, a person's character, disposition, attitude and personality are reflected in the sentences he speaks to the opponent. The method used in this study is a qualitative method that is descriptive. The descriptive method was used to describe the implementation and violation of the maxim of civility at the Interview of Deddy Corbuzier and Fadilah Supari (Former Minister of Health of the Republic of Indonesia). Based on the results of the analysis and discussion of